PENGEMBANGAN E-MODUL TERINTEGRASI POTENSI LOKAL GUNUNG KIJANG PADA MATERI BIOTEKNOLOGI DALAM BIDANG AGRIBISNIS DAN AGROTEKNOLOGI UNTUK KELAS X SMK - Fianti Juliantika; Nevrita Nevrita; Azza Nuzullah Putri (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
This study aims to develop teaching materials in the form of an integrated e-module of Gunung Kijang's local potential on biotechnology materials in the fields of agribusiness and agrotechnology for class X SMK students, and describe their quality in terms of validity, practicality and effectiveness. This research is a research and development (research and development) using the hannafin and peck development research model consisting of three stages, namely the needs analysis phase, the design phase and the development or implementation phase and each phase involves evaluation. The instruments used were material expert validation sheets and teaching materials experts, teacher and student practicality sheets, pre-test and post-test evaluation sheets, and student learning interest questionnaires after using e-modules. Based on the results of development research, it is known that the assessment of the validity of the aspects of the material and teaching materials is categorized as "very valid". The results of the practicality questionnaire by teachers and students belong to the “very practical” category. The results of the effectiveness through the pre-test and post-test showed an increase with the n-gain value in the high category, the student learning interest questionnaire showed an increase with the n-gain value in the medium category. It can be concluded that the development of an integrated e-module of Gunung Kijang's local potential in biotechnology materials in the fields of agribusiness and agrotechnology for class X SMK students is developed very validly, practically, and effectively so that it is suitable for use in the learning process at school.Kata Kunci: Biotechnology, E-Modules, Local Potential